Effects of Daily Read-Alouds on Students' Sustained Silent Reading - Lauren A. Pegg; Frederick J. Bartelheim (Arizona State University, 2011)
This action research project investigated the effects of daily teacher read-alouds on first graders' ability to sustain silent reading for an extended length of time. Students' enjoyment of silent reading was also investigated. The data on ability to sustain silent reading was collected from timed silent reading experiences, and a pre and post survey completed by students on their enjoyment and performance during silent reading time. The findings of the study suggest an increase in the length of time students silently read to themselves as a result of daily teacher read-alouds. Additionally, survey comments suggested an increase in enjoyment of silent reading as a result of the daily read-alouds.